Quality Teaching: Relationship between Increased Enrollment of Students and Teaching Efficacy - Dr. Ijaz Hussain; Dr. Masood Ahmad; Muhammad Aqeel; Dr. Muhammad Irfan Malik (Al-Qanṭara, 2023)
The current study sought to determine the relationship of increased enrollment of the students and teaching efficacy. The study employed the descriptive survey research design. The study was delimited to public sector primary schools of tehsil Dera Ghazi Khan. Purposive sampling technique was used. 317 sample size (233 teachers and 84 head teachers) working in public sector primary school in tehsil Dera Ghazi Khan were selected. Questionnaire was used as tools for data collection. Data was analyzed using statistical techniques, t–test, correlational and regression analysis. The results of data analysis were presented using frequency distribution and the t-test, Pearson correlation and regression. Strong negative correlation -.703 was found. No statistical significant difference was found in the perception teachers and head teachers. The study recognized that high enrolment trends in schools led to overworking the staff members, inadequate teaching facilities, poor infrastructure of school and ultimately affects the teaching efficacy. The increased enrolment impacted to a great extent on the quality of teaching in public primary schools. Based on the findings of the study. It is recommended that the government should take necessary measures in providing facilities that match the pupils’ enrolment to ensure quality education at public sector primary schools. Keywords- Quality Teaching, Increased Enrollment of Students and Teaching Efficacy